2013
DOI: 10.1111/josh.12116
|View full text |Cite
|
Sign up to set email alerts
|

Survey of New Mexico School Health Professionals Regarding Preparedness to Support Sexual Minority Students

Abstract: School health professionals in New Mexico do not appear prepared to address needs of LGBTQ students. Schools should consider integrating specific content about LGBTQ health risks and health disparities in trainings regarding bullying, violence, cultural competency, and suicide prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
2
31
0
5
Order By: Relevance
“…Health risk behaviors and subjective perception of an individual’s own health, including depression, have been shown to be negative among LGB youths who lack parental support [15, 23, 31, 33]. Also, in order to decrease SROs among youths there is a need to improve the negative impression and attitude that society displays towards homosexuals, and a need to establish anti-bullying policies towards LGB youths [28, 34]. On the same note, family-based interventions can decrease hopelessness and depression, thereby leading to less suicide attempts [35].…”
Section: Discussionmentioning
confidence: 99%
“…Health risk behaviors and subjective perception of an individual’s own health, including depression, have been shown to be negative among LGB youths who lack parental support [15, 23, 31, 33]. Also, in order to decrease SROs among youths there is a need to improve the negative impression and attitude that society displays towards homosexuals, and a need to establish anti-bullying policies towards LGB youths [28, 34]. On the same note, family-based interventions can decrease hopelessness and depression, thereby leading to less suicide attempts [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a lack of students feeling safe or willing to talk to nurses about topics related to sexual orientation or attraction, other researchers have found nurses may not be adequately prepared to meet the needs of sexual minority youth (Mahdi, Jevertson, Schrader, Nelson, & Ramos, 2014; Saewyc, Bearinger, McMahon, & Evans, 2006). A study based on data collected in 2010 from school nurses, counselors, and social workers in New Mexico found that school nurses were less likely than school counselors and social workers to report high or moderate knowledge of health risks for LGBTQ youth.…”
Section: Discussionmentioning
confidence: 99%
“…Los conocimientos sobre comportamientos sexuales son estadísticamente más bajos que los otros dos tipos de conocimientos evaluados. La falta de conocimiento sobre temas concernientes a la diversidad sexual no toca solamente al futuro personal docente aquí evaluado o a otros profesionales del sector de la educación como psicólogos y consejeros escolares y trabajadores sociales (Mahdi, Jevertson, Schrader, Nelson & Ramos, 2014;Savage, Prout & Chard, 2004). Según investigaciones efectuadas en varios países, estudiantes y profesionales del sector salud (médicos, enfermeros, cirujanos, fisioterapeutas, entre otros) evidencian igualmente conocimientos insuficientes sobre las realidades de las personas LGB.…”
Section: Discussionunclassified
“…Igualmente, respecto al sector de la educación, el desconocimiento de temas relacionados con la población LGB es preocupante. Por ejemplo, psicólogos, consejeros escolares y trabajadores sociales en Estados Unidos obtuvieron resultados bajos y moderados en los conocimientos sobre realidades de adolescentes homosexuales y bisexuales evidenciando, y tienen una baja preparación para proporcionar un ambiente seguro al estudiantado LGB en sus instituciones educativas (Mahdi, Jevertson, Schrader, Nelson & Ramos, 2014;Savage, Prout & Chard, 2004). Por otra parte, la literatura muestra cómo las actitudes hacia las personas y el estudiantado LGB siguen siendo negativas en Colombia (Brigeiro, Castillo & Murad, 2009;Cantor, 2008).…”
Section: Problemaunclassified